Kelayakan Lembar Kerja Siswa (LKS) Berbasis Proyek Untuk Pembelajaran IPA di SMP - Yanti Nur Kholilah; I Ketut Mahardika; Sutarto Sutarto (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2016)
The study is a result of developmental research. The purposes of the research is to produce a project base worksheet that appropiate for science learning in junior high school. The design of the research is 4-D. The appropiatness of the worksheed is ditermined by four aspects: content, languistic, appearance, and layout (kegrafikaan). The appropiatness of content is determine by score of expert validators and the improvement of students’ cognitive achievement. The linguistic aspect is found through linguistic expert validator and legibility aspect is determined by legibility of worsheet and students’ responses to the worksheet. Aspect of layout (kegrafikaan) is obtained from score of expert validators and students’ responses through quitionair. The reseach was conducted to students class VII SMP Muhammadiyah Bondowoso, even semester year 2015-2016. Findings of the study shows that the appropiateness of four aspects are 85; 87,5; 87,5; 87,5 respectively. Most of the aspects are in very appropriate criteria. So, the study can be concluded that the worksheet model is very appropiate for science learning in junior high school.